PENYULUHAN ETIKA BERBUSANA ADAT KE PURA DI DESA JUNGUT KECAMATAN BAJARANGKAN KABUPATEN KLUNGKUNG - I Gusti Ayu Nilawati; Putu Krisna Adwitya Sanjaya (UNHI Press, 2020)
Clothing is one of the characteristics of individuals in performing well in carrying out activities according to their role and status in living life, such as many who experience changes in the ethics of traditional dress to Temple (Pura). Since ancient times, custom clothing to the temple has always changed according to the times. should in traditional dress, especially to the temple must be in accordance with the applicable standard, but in its development now some Hindus, especially teenagers are still found using traditional clothes that deviate from the standard. Extension activities are conducted in Jungut Village, starting with an introduction, then giving open questions to participants about the material provided. After the material was finished, participants were given the opportunity to ask questions. Next is a tutorial and finally participants can do a simulation independently in using traditional clothes. Extension activities ended with giving questions to determine the participants' understanding. The results of the extension program can be summarized as follows: Extension of traditional dress to temple is a solution in increasing public understanding of good and right dress ethics in conducting worship activities to the temple, counseling with tutorial methods is seen as quite effective in increasing public understanding in using traditional clothing good and right.